Accuracy of Approximation for Discrete Distributions. (8th November 2016) - Móri, Tamás F.
Abstract : The paper is a contribution to the problem of estimating the deviation of two discrete probability distributions in terms of the supremum distance between their generating functions over the interval[ 0, 1 ] . Deviation can be measured by the difference of thek th terms or by total variation distance. Our new bounds have better order of magnitude than those proved previously, and they are even sharp in certain cases.